Perceptions of Antibiotic Therapy Among Nursing Home Residents: Perspectives of Caregivers and Residents in a Mixed Exploratory Study - Mathieu Ahouah; Corinne Lartigue; Monique Rothan-Tondeur (MDPI AG, 2019)
Antimicrobial resistance is a major public health threat worldwide. Some authors have suggested that end-users of nursing homes have an influence on antibiotic prescribing. The objective of this study is to describe the views of end-users and professionals on residents’ behavior towards antibiotic therapy in terms of knowledge, beliefs, and attitudes towards this drug class and its prescribing process. This is a concurrent mixed methodology study using questionnaires and semi-directive individual interviews with nursing homes residents, nurses, and doctors practicing in these facilities. The questionnaires analyzed were collected from 35 residents (24.3%) and 109 nurses (75.7%). The qualitative interview involved 26 of total participants that agreed to be interviewed. We noticed misconceptions being held by the residents regarding the antibiotic resistance phenomenon. Additionally, nurses were not considered as a source of information about antibiotics. Nurses and residents had conflicting opinions about residents requesting antibiotics, and the findings depict a stereotypical view of the nurse profession as a reflection of a cognitive representation. The authors conclude that, despite many campaigns, further efforts are needed to tackle antimicrobial resistance. Initiatives could include raising awareness about antimicrobial resistance, clarifying the role of nurses, and communicating well with residents about their needs in nursing homes.